2021
DOI: 10.1111/1475-6765.12482
|View full text |Cite
|
Sign up to set email alerts
|

Cabinet ministers and inequality

Abstract: Scholars and commentators increasingly wonder whether governments' failure to address socio-economic inequalities is the result of unequal representation. Recent literature on policy responsiveness in the United States and Europe finds evidence that party and parliamentary policy proposals and actual policy outcomes are closer to the preferences of the rich than of the poor. However, the extent and character of such unequal representation remains thinly understood. Among the most thinly understood are the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
(186 reference statements)
0
5
0
Order By: Relevance
“…Elected representatives in Germany, the Netherlands, Norway, and Sweden are less likely to be multimillionaires than their American counterparts, but they come overwhelmingly from the ranks of university-educated professionals and tend to belong to the top two or three deciles of the income distribution (see Carnes and Lupu's contribution to this volume). A growing number of studies show that occupational background and associated life circumstances and social networks influence the policy preferences and priorities of elected officials across a wide range of different national contexts (Alexiadou 2022;Carnes and Lupu 2015;Hemingway 2020;O'Grady 2019;Persson 2021;Curto-Grau and Gallego in this volume). In a related vein, recent studies find that elected representatives tend to be more accurate in their perceptions of the preferences of affluent citizens than in the perceptions of the preferences of poor citizens (Pereira 2021;Sevenans et al 2020).…”
Section: Rethinking Unequal Responsivenessmentioning
confidence: 99%
“…Elected representatives in Germany, the Netherlands, Norway, and Sweden are less likely to be multimillionaires than their American counterparts, but they come overwhelmingly from the ranks of university-educated professionals and tend to belong to the top two or three deciles of the income distribution (see Carnes and Lupu's contribution to this volume). A growing number of studies show that occupational background and associated life circumstances and social networks influence the policy preferences and priorities of elected officials across a wide range of different national contexts (Alexiadou 2022;Carnes and Lupu 2015;Hemingway 2020;O'Grady 2019;Persson 2021;Curto-Grau and Gallego in this volume). In a related vein, recent studies find that elected representatives tend to be more accurate in their perceptions of the preferences of affluent citizens than in the perceptions of the preferences of poor citizens (Pereira 2021;Sevenans et al 2020).…”
Section: Rethinking Unequal Responsivenessmentioning
confidence: 99%
“…While such a link between descriptive and substantive representation has been empirically established for other social groups, most notably women (Höhmann 2020, Volden et al 2018, Wängnerud 2009, the empirical evidence on the influence of legislators' class backgrounds is just beginning to emerge. Adopting different methodological approaches, existing studies confirm that the socioeconomic background of legislators influences not only their priorities and opinions but also their behavior in office (Alexadiou 2022, Barnes et al 2021, Borwein 2021, Carnes 2012, Carnes & Lupu 2015, Grumbach 2015, Hayo & Neumeier 2012, O'Grady 2019.…”
Section: Policy Responsiveness: Biased Decisions?mentioning
confidence: 99%
“…Using data from 18 parliamentary democracies, Alexadiou (2022) analyzes whether the class composition of cabinets affects welfare generosity. Even when she takes the partisan composition of cabinets into account, there remains a substantial effect of ministers' class backgrounds.…”
Section: Policy Responsiveness: Biased Decisions?mentioning
confidence: 99%
“…Government responsiveness is considered one of the most important features of democracy (Dahl, 1971;Powell, 2004;Verba & Nie, 1972) and previous studies have examined what kinds of variables explain variations in government responsiveness. It has been revealed that government responsiveness tends to be determined by social media (Ennser-Jedenastik et al, 2022;Eom et al, 2018;Panagiotopoulos et al, 2013), regime types (Cleary, 2007;Grossman & Slough, 2022;Powell, 2004), party organization (Linde & Peters, 2020), cabinet ministers' professional backgrounds (Alexiadou, 2022), and socio-economic conditions of countries or provinces (Itani et al, 2022;Speer, 2012).…”
Section: Publicmentioning
confidence: 99%